Investigation on the regenerative Brayton refrigeration cycle performances using novel Mn-Fe-P-Si composite material with thermal hysteresis as the working medium. (March 2022) - Li, Yan; Huang, Bowei; Lin, Guoxing; Chen, Jincan; Brück, Ekkes
Highlights: A Brayton refrigeration cycle with novel MnFe-based composite material is proposed. Experimental and theoretical researches are fully integrated. Effects of thermal hysteresis on the cycle performance are discussed. The main thermodynamic quantities of the refrigeration cycle are calculated. Thermodynamic quantities with composite and constituent materials are compared. Abstract: MnFeP(As, Ge, Si) series compounds are three kinds of MnFe-based magnetocaloric materials, which have giant magnetocaloric effect. In this work, the experimental characteristic curves of new style Mn-Fe-P-Si materials, numbered as 1: Mn1.32 Fe0.67 P0.52 Si0.49, 2: Mn1.37 Fe0.63 P0.5 Si0.5, and 3: Mn1.35 Fe0.66 P0.5 Si0.5 are presented. Based on the experimental data of these component materials and thermodynamic analysis method, a novel composite material is put forward. The optimal molar mass ratios of the composite material are obtained and they are 0.22, 0.33, 0.45, respectively. A regenerative Brayton refrigeration cycle employing the optimal composite material with thermal hysteresis as the working medium is built. By numerical calculation, the influences of thermal hysteresis on the main thermodynamic quantities are evaluated. The results show that the thermal hysteresis of the working medium results in a decrease of 13.6%, 14.6%, 18.8%, and 16.1% of the cooling quantity, net cooling quantity, optimally working temperature range, and coefficient of performance, respectively. These conclusions are beneficial to the optimal parameter design and performance improvement of active magnetic refrigerators.